Leprosy trends at a tertiary care hospital in Mumbai, India, from 2008 to 2015 - Thirumugam Muthuvel; Petros Isaakidis; Hemant Deepak Shewade; Lucy Kattuppara; Rajbir Singh; Srinivas Govindarajulu (Taylor & Francis Group, 2016)
Background: Leprosy remains an important cause of preventable disabilities. After the advent of multidrug therapy, new leprosy cases have come down dramatically. Despite this achievement, India, which contributes 60% of the global leprosy burden, faces some challenges to eliminate the disease, including active transmission in the community and delayed diagnosis of leprosy patients. Objectives: The objectives of the study were 1) to determine sociodemographic and clinical characteristics of newly diagnosed adults and children (less than 15 years) with leprosy and their trends over time (2008-2015) and 2) to describe the profile of surgical procedures among leprosy patients registered for reconstructive surgeries during 2006-2015. Design: Retrospective descriptive study was conducted involving a record review of new patients with leprosy registered in Vimala Dermatological Centre, Mumbai. Results: A total of 578 new leprosy cases were registered in the hospital during 2008-2015. There has been a steady increase in the trend of child cases (less than 15 years) registered in the facility (from 3% in 2008 to 18% in 2015), x 2=12.11, p<0.01. The majority of the patients (68%) were migrants of Uttar Pradesh and Bihar. Conclusions: Targeting children and migrants and ensuring early diagnosis and treatment initiation are essential components for leprosy elimination in an urban metropolis in India.